Measuring and Promoting Wellbeing - Podger, Andrew (ANU Press, 2014)
"Australia continues to be at the forefront of international work on measuring and promoting wellbeing, Ian Castles being a significant contributor over the last forty years as an official and academic. This book combines a selection of Castles' important work with contemporary research from a range of contributors. The material is in four parts: 1. The role of economics in defining and promoting wellbeing 2. Measuring real income and wellbeing 3. Measuring inequality 4. Climate change and the limits to growth. The issues canvassed are both long-standing and current. Does economic growth contribute to wellbeing? How different is income to wellbeing? How do we measure societal wellbeing and take its distribution into account? The book will be of value to all those looking to informed debate on global challenges such as reducing poverty, sustaining the environment and advancing the quality of life, including politicians, commentators, officials and academics."